Clinicopathologic features of the nine patients with primary diffuse large B cell lymphoma of the breast - DANE, FAYSAL (SPRINGER HEIDELBERG, 2011)
Non-Hodgkin lymphomas of the breast are uncommon cancers that occur as either primary extranodal diseases or secondary localizations of a systemic disease. The term primary breast lymphoma (PBL) is used to define malignant lymphomas primarily occurring in the breast in the absence of previously detected lymphoma localizations. In this report, we analyzed nine patients with primary diffuse large B cell lymphoma (DLBCL) of breast. Patients with newly diagnosed PBLs treated between 1997 and 2009 in five institutions were retrospectively evaluated. The median age of the patients with PBL was 49 years (range 30-82 years), and four patients had left-sided and five had right-sided disease. All of the nine patients were classified as DLBCL. Five patients with DLBCL received chemotherapy followed by involved-field or elective-field radiotherapy and four received chemotherapy alone. Complete remission (CR) following primary treatment for all patients with PBL except for two cases was obtained. In two patients, recurrence occurred. At the median follow-up of 24.2 months, the 5-year OS rate was 76.2%. Univariate analysis indicated that age, ECOG PS, clinical stage, international prognostic index score, lactate dehydrogenase levels and the presence of B symptoms were not important prognostic factors in our study. Our series contained a small sample size, but it is interesting because it included only DLBCL cases. However, definitive conclusions about treatment and follow-up options of patients cannot be made in such a small series of patients. There are very few reports of patients with PBL treated with R-CHOP rather than CHOP alone. The followup is probably still too short and sample size very few to know how R-CHOP compares with CHOP-treated patients in other series, but this is definitely worth looking at in more detail when reasonable median follow-up has been achieved and sample size are sufficient.
Keywords: Primary breast lymphoma; Diffuse large B cell lymphoma; Radiotherapy; Chemotherapy; NON-HODGKIN-LYMPHOMA; MALIGNANT-LYMPHOMA; PROGNOSTIC-FACTORS